Telling adults about one's plight as a victim of bullying: Student- and context-related factors predicting disclosure - Blomqvist Katri; Saarento-Zaprudin Silja; Salmivalli Christina (Blackwell Publishing Ltd, 2022)
We examined student‐ and context‐related factors related to whether bullied students tell adults about their plight at school or at home. The sample included 1,266 students in primary (Grades 4–6) and lower secondary (Grades 8–9) schools, who had answered an online questionnaire at two measurement points about 5 months apart and were identified as victims of bullying on the basis of the latter. Only 55.4% of the bullied students had told their situation to someone, and much fewer had told an adult. Telling an adult at home was more common (34.0%) than telling a teacher (20.6%) or some other adult at school (12.7%). In a longitudinal structural equation model (SEM), factors related to increased likelihood of telling an adult were female gender, lower grade level, the chronicity of victimization, perceived negative teacher attitude towards bullying (teacher not tolerating bullying), and perceived peer support for victims (classmates’ tendency to defend students who are victimized).